E-Modul IPAS Berbasis Aplikasi Flip PDF Corporate Untuk Mendukung Implementasi “Kurikulum Merdeka” di Sekolah Dasar - Ira Oktaviani; Desyandri Desyandri (Universitas Negeri Padang, 2023)
This research is motivated by the lack of interest in the teaching materials used in elementary schools. The aim of the research is to produce valid and practical e-modules using Corporate Flip Pdf in supporting the successful implementation of the